MASTERING THE ART OF ORAL FLUENCY: A MULTIDIMENSIONAL ANALYSIS OF SECOND LANGUAGE SPEAKING - Tolibjonova Munisa; Xolnazarova Dinara; Poʻlatova Sevinch (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article provides a comprehensive and multidimensional exploration into the fundamental  dimensions  of  speaking  competence  within  the  framework  of  second language (L2) acquisition. In the realm of contemporary applied linguistics, achieving oral  proficiency  is  recognized  as  one of  the  most  complex  challenges  for  learners, involving  a  sophisticated  interplay  of  cognitive,  linguistic,  and  social  factors.  This study meticulously examines the intricate balance between the three core pillars of the CAF framework: Complexity, Accuracy,  and Fluency. By addressing the cognitive demands imposed on learners during real-time communication, the article analyzes how  mental  processing  constraints  impact  speech  production.  Furthermore,  the research highlights the critical role of psycholinguistic processing models, specifically Levelt’s model of speech production, and explores how socio-pragmatic adaptation contributes  to  achieving  advanced  levels  of  proficiency.  The  authors  argue  that successful  L2  speakers  do  not  merely  memorize  vocabulary,  but  rather  undergo  a cognitive  transition  from  controlled,  laborious  processing  to  the  automatization  of speech  production  through  sustained  practice  and  the  strategic  application  of communicative  competence.  Detailed  attention  is  given  to  strategic  competence—including circumlocution and self-correction—as a vital mechanism for maintaining flow  despite  linguistic  gaps.  Additionally,  the  paper  investigates  the  impact  of pragmatic  awareness  on  learner  success,  emphasizing  that  near-native  proficiency requires an understanding of cultural nuances and register differences. Ultimately, this article  aims  to  synthesize  theoretical  models  with  practical  implications  for  both learners and educators, providing a clear pathway toward  mastering the art of oral fluency in a second language. The findings suggest that a holistic approach, integrating cognitive  development  with  social  awareness,  is  essential  for  fostering  genuine communicative autonomy in diverse linguistic contexts.